Adolescence - Steinberg, Laurence D. 1952- (McGraw-Hill Higher Education, 2005)
In this trusted text, world-renowned researcher and author Laurence Steinberg presents the scientific study of adolescence in a clear and accessible writing style. Theories and research methods are integrated into each chapter. The text emphasizes depth of research and stresses the fact that the context in which adolescents live affects their behavior and social relationships. The new seventh edition is supported by an innovative supplements program for instructors as well as students.